Pear drying: Perspectives for convective drying and nutritional evaluation - Guiné, Raquel (2013)
The present study aimed the evaluation of the possibilities of introducing alterations in the method used traditionally to dry pears in Portugal, by direct open-air sun exposure, in order to modernize it, making it possible to be used in an industrial scale, being more profitable and allowing the obtaining of dried pears with a better quality. One other objective of the present study, apart from the simplification of the traditional method, was to infer about the possibility of using alternative varieties for the production of the dried pears. Therefore, pears of different varieties were dried under different conditions (solar drying with the complex traditional method with different stages of drying and convective air draying, in a single continuous stage, at 30, 40 and 50ºC). They were then analysed in terms of their physical attributes and chemical properties, for comparison. It was possible to conclude that the complexity of the traditional method can be avoided by doing the drying in a continuous stage at constant temperature, in a convective drier, without compromising the final quality of the product. One other conclusion that was drawn from this study was that other varieties different from the S. Bartolomeu, which is traditionally used to produce dried pears, can be used with success allowing the obtaining of died pears with very good properties.